The factor contributing to the learners success in language learning (Conference on English Language Teaching, 2023)
Learning involves not only a matter of intellectual exercise, but a matter of emotions as well. The situation of inner most self of individuals to great extent can effect their learning drives. Several studies on learners motivation show that the emotion states of language learners plays an important role in determining their achievements. There are some internal and external factors can be identified to give contribution to the learners success in language learning, for examples: having high motivation, high self confidence, avoiding learners anxiety, having good image, creating positive climate, providing speech community and developing English practice, language learning refers to habit formation process, good teacher-learner relationship and creating English learning as enjoyable and knowledge satisfying Experience.